Dispersion mechanism of nanoparticles and its role on mechanical, thermal and electrical properties of epoxy nanocomposites - A Review - SINGH, Baljit; MOHANTY, Akash; SRIVASTAVA, Amit Kumar; SINGH, Ajay (Journal of Metals, Materials and Minerals, 2023)
The combined effect of nano-reinforcements on the mechanical performance of nanocomposites, which are a novel class of epoxy matrix hybrid nanocomposites containing multiwall carbon nanotubes (MWCNT), graphene, and nanodiamonds (NDs), is drawing substantial attention from many research communities. The discussion concentrates on the dispersion techniques adopted for the preparation of epoxy composites containing different types of nanoparticles (3-D fillers, nanofibers, nanotubes, and plate-like fillers). This review paper covers the electrical, thermal, and mechanical properties of carbon nanotubes (CNTs), graphene, and nanodiamond-reinforced epoxy nanocomposites and correlates them with the topographical features, morphology, weight fraction, dispersion state, and surface functionalization of CNTs, graphene, and nanodiamond. This review paper also summarises recent developments in the dispersion method of different carbon nanoparticles in epoxy matrix.